2015
DOI: 10.1016/j.biomaterials.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal proliferation of human stromal cells adjusts to nutrient availability and leads to stanniocalcin-1 expression in vitro and in vivo

Abstract: Cells and tissues are intrinsically adapted to molecular gradients and use them to maintain or change their activity. The effect of such gradients is particularly important for cell populations that have an intrinsic capacity to differentiate into multiple cell lineages, such as bone marrow derived mesenchymal stromal cells (MSCs). Our results showed that nutrient gradients prompt the spatiotemporal organization of MSCs in 3D culture. Cells adapted to their 3D environment without significant cell death or cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…Previous reports have shown that STC1 is upregulated in different 3D culture systems. [14][15][16][17] We have previously shown that hMSCs in 3D electrospun (ESP) scaffolds have fewer stress fibers and focal adhesions than in 2D. 35,36 We have also seen that 3D alginate hydrogels show the same trend, in line with results published by others.…”
Section: Increased Stc1 Secretion In 3d Culturessupporting
confidence: 87%
See 1 more Smart Citation
“…Previous reports have shown that STC1 is upregulated in different 3D culture systems. [14][15][16][17] We have previously shown that hMSCs in 3D electrospun (ESP) scaffolds have fewer stress fibers and focal adhesions than in 2D. 35,36 We have also seen that 3D alginate hydrogels show the same trend, in line with results published by others.…”
Section: Increased Stc1 Secretion In 3d Culturessupporting
confidence: 87%
“…13 STC1 has also been reported to increase in 3D culture platforms, such as spheroids and 3D-additive manufactured scaffolds, compared to 2D cultures such as tissue culture polystyrene (TCP). [14][15][16][17] Despite these efforts, the molecular mechanisms by which STC1 expression and secretion are regulated are still unclear.…”
mentioning
confidence: 99%
“…They also expressed high levels of three anticancer proteins: IL-24, TNFα-related apoptosis-inducing ligand, and CD82. 15 , 47 STC1 transgenic mice do not show any carcinogenic character in their natural history. 48 Intermittent inhalation of STC1 might be safe in terms of carcinogenesis, but further data are needed to confirm its safety as a treatment for IPF.…”
Section: Stc1 Has Myriad Functions: the Possibility Of Covering Complmentioning
confidence: 93%
“…As the cells divided over time and started to occupy the empty pores in the scaffolds, they disposed themselves in a spiral-like shape, which is typical of hMSCs growth in these scaffolds as previously observed. [60,61] At instances, where the pore is in the process of filling, it will be referred to as a filling pore. A filled pore on the other hand will denote a pore completely filled with cells.…”
Section: Scaffold Toxicitymentioning
confidence: 99%